Technical Challenges in Shifting from BS IV to BS-VI Automotive Emissions Norms by 2020 in India: A Review - Devendra Vashist; Naveen Kumar; Manu Bindra (Archives of Current Research International, 2017)
Automotive vehicles emit several exhaust gases and pollutants. The largest part of these gases consists of nitrogen (N2), water vapor (H2O) and carbon dioxide (CO2) these are not toxic. Harmful gases i.e carbon monoxide (CO) produced because of incomplete combustion, nitrogen oxides (NOx) generated at high temperatures, hydrocarbons (HC) obtained from unburnt fuel, particulate matter (PM, mostly soot) and oxides of sulphur (SOx) due to sulphur content in fuel, are referred as pollutants. India’s Emission Standard were formulated in 1991 has reached today to direct transition to BS VI from BS IV norms. This decision to leapfrog fuel standards has managed to disrupt oil and auto Industry. In this paper challenges faced by these industries for this transition based on technical understanding are discussed. For diesel engines diesel particulate filter for moving to BS V and Selective Catalytic Reduction for BS VI is critically analyzed. For S.I engines technologies that are likely to be commercialized which will help vehicles to comply with BS VI norms are explained. Technology up gradation, its validation and assimilation of this technology by customers are some of the major issues faced by the auto sector. Reduced time line, selection of appropriate technology for refining, revamping of the existing units and simultaneous distribution of two types of oil are the major challenges faced by the oil refineries. An investment of Rs. 1.5 lakh crore by automotive industry and Rs 80,000 crore by oil refineries has to be made for up gradation to BS VI by 2020.